Social enterprise and the wider community: one possible model. (2016) - Oham, Charles A.C.; Pestano, Catherine; Allen, Jerry
The paper, based on a case study, uses Gibbs Reflective Cycle (1988) to analyse a recent partnership initiative between university academics and a drug and alcohol agency. The project involved training a cohort of mature students affected by drugs and alcohol and assisting them to find new purpose - running their own businesses as social entrepreneurs. The profile of the beneficiaries on the training included people presenting with backgrounds of mental health, drug and alcohol use, other disabilities and ex-offenders. The enterprise has been identified as a key contributor to student employability by improving graduate outcomes. This project adds another new factor to the discussion - that of social enterprise, the social 'bottom line' and explores the extent to which this fits with the university business objectives. Reflective and reflexive learning from two cohorts is presented with this case study; the aim is to stimulate wider discussion on the value of such a model and to highlight the importance of reflection in entrepreneurial education design and delivery.